Identification of Soil Bacteria in Several Paddy Fields (Oryza sativa L.) in Wita Ponda District - Novita Christanty Pasaungan; Nadine Sandra Agustina; Epriani Rimbun; Rahmat Hidayat (International journal of technology and education research, 2025)
Rice (Oryza sativa L.) is a major agricultural commodity in Wita Ponda District and serves as the primary livelihood and economic support for local communities. However, rice productivity in this area remains relatively low, partly due to limited farmer knowledge regarding crop management and insufficient information on soil conditions, particularly soil nutrient content. This study aimed to identify soil bacteria present in paddy fields (Oryza sativa L.) in Wita Ponda District. The research was conducted from March to May 2024. Soil samples were collected from five locations in Wita Ponda District at a depth of 0–20 cm. One composite soil sample from each location was used for bacterial identification as well as for soil pH and organic carbon (C-organic) analysis.The results showed that a total of 1,184 bacterial isolates were identified from paddy fields located in Lantula Jaya, Bumi Harapan, Puntari Makmur, Emea, and Solonsa Jaya villages. Among these, 362 distinct bacterial isolates were grouped into four genera: Azotobacter (119 isolates), Bacillus (45 isolates), Marinococcus (181 isolates), and Corynebacterium (17 isolates). Soil pH values ranged from slightly acidic to neutral, with values of 6.49, 6.44, 6.90, and 6.68. Soil organic carbon content ranged from low to moderate, with values of 1.18%, 1.37%, 2.44%, 1.16%, and 1.81%.